2004
DOI: 10.1186/gb-2004-5-10-r77
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Complete genome sequence of the industrial bacterium Bacillus licheniformis and comparisons with closely related Bacillus species

Bacillus licheniformis is a Gram-positive, spore-forming soil bacterium that is used in the biotechnology industry to manufacture enzymes, antibiotics, biochemicals and consumer products. This species is closely related to the well studied model organism Bacillus subtilis, and produces an assortment of extracellular enzymes that may contribute to nutrient cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(145 citation statements)
references
References 53 publications
5
137
0
3
Order By: Relevance
“…In contrast, the YkuV protein we cloned could easily be expressed in E. coli. In addition, the new protein sequence containing this difference is locally well aligned with its homolog, the YkuV protein from Bacillus licheniformis, which is considered the closest relative species of B. subtilis (51). Furthermore, the secondary structure prediction in combination with the homology modeling indicated that the altered residues do not change the secondary structures, and the extended residues have no effect on the global fold.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, the YkuV protein we cloned could easily be expressed in E. coli. In addition, the new protein sequence containing this difference is locally well aligned with its homolog, the YkuV protein from Bacillus licheniformis, which is considered the closest relative species of B. subtilis (51). Furthermore, the secondary structure prediction in combination with the homology modeling indicated that the altered residues do not change the secondary structures, and the extended residues have no effect on the global fold.…”
Section: Resultsmentioning
confidence: 97%
“…MC-1) showed no channel activity in previous studies (7). Of the bacteria containing the remaining 26 homologues, six of them were commercially available: B. licheniformis, isolated from soil and plant material (27), and L. vestfoldensis (28), R. sphaeroides (29), S. putrefaciens (30), R. denitrificans (31), and Oceanicaulis sp. (32) isolated from sea water (28 -33).…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus licheniformis is a Gram-positive, spore-forming soil bacterium that is used for the production of enzymes, antibiotics, biochemicals and consumer products on an industrial scale (Li, Yang, & Mu, 2010;Rey et al, 2004;Xie, Guan, & He, 2012). Previously, sequence homology-based studies revealed the identity of proteins involved in the production of antibiotics, leading to the detection of two mesarcidin-like peptide lichecidins in the cell-free culture supernatant of B. licheniformis (ATCC 14580 and DSM 13, respectively).…”
Section: Introductionmentioning
confidence: 99%